Effects of the semi-occluded vocal tract therapy on acoustic parameters of the voice teachers - Vásquez Burgos, Karina (2016)
The goal of this research is to analyze the effect of therapy Vocal Tract semi-occluded on the acoustic parameters of the voice in elementary school teachers of the commune of Chillán. This research is in the population of teachers, principal group of professionals who need to use your voice for long periods; so they are more likely to suffer from vocal disorders. This research proposes therapy Tract Vocal semi-occluded, because according to authors like Guzman, Titze, Belhau among others, provides immediate results while maintaining the acoustic parameters pitch and intensity, allowing the voice quality is maintained, thus avoiding suffering dysphonia. That is, the speech therapy responsible for implementing and vocal warm-up exercises cooling in order to avoid negative effects on acoustic parameters tone and intensity. Methodologically is oriented towards the quantitative paradigm, descriptive and comparative type. Regarding the design is quasi-experimental and longitudinal type. To this effect the acoustic voice parameters were measured using the program acoustic analysis of voice Praat in an experimental and control group. Regarding the results obtained positiveeffects on acoustic voice parameters it was evident, proving the effectiveness of semi-occluded vocal tract therapy.